ASSESSMENT OF PHYSICS PROBLEMS POSED BY STUDENTS - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2010)
A scoring rubric and its criteria of assessing students' posed problems were developed in this study. The research was conducted in the university first year introductory physics course in the 2008-2009 academic year. Sixty students were participated to the study. Data of the research were collected, from students' worksheets and reviews with the students, to find out the scoring criteria of the rubric. Six criteria were determined which are fluency of the problem, scientific accuracy of the problem, the number of equations needed to solve problems, number of questions asked from the problem situation, the type of problem according to complexity and the solvability of the problem. It was found that; Inter-rater reliability coefficient r = 0.86 and Intra-rater reliability coefficient r = 0.92.
Keywords: Problem Posing; Analytic Rubric; Performance Assessment